PENGARUH MODEL GROUP INVESTIGATION TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN TEMATIK - Wulandari, Sindi; Kartono, Kartono; Salim, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
the model of group investigation in thematic learning to the learning outcomes of fifth-grade students of Elementary School 36 Pontianak Selatan. The research method in this research was a quasi-experimental with the non-equivalent control group experimental design. This research used total population sampling with the total population were 51 students of fifth-grade students of Elementary School 36 Pontianak Selatan. The techniques of data collection were measurement technique and direct observation technique. The tools of data collection in this research were test in form of multiple choice with the total of 45 questions and assessment rubrics. Statistical calculations showed that average cognitive domain learning outcomes of the experimental class were 73,60 and control classes were 69,65 obtained ?????? (2,289) > ?????? (2,012) it means Ha was accepted. Psychomotor domain the average learning outcomes of the experimental class were 74,74 and control classes were 73,31 obtained ?????? (2,51) > ?????? (2,012) it means Ha was accepted.. The effect size (ES) were 0,42 (medium). The results of this research was the group investigation model in thematic learning had a moderate effect on the learning outcomes of fifth-grade students of Elementary School Pontianak SelatanKeywords: Effect, Group Investigation Learning Outcomes.